SURVIVING A LARYNGECTOMY: THE VIEWS OF POST-OPERATIVE CANCER PATIENTS AND THEIR FAMILIES - Steyn, Hendriëtte; Green, Sulina (Social Work/Maatskaplike Werk, 2018)
Major advances in cancer detection and treatment options have now afforded cancer patients the prospect of a longer life. This places various demands upon patients, families and social workers in the field of oncology. A combination of quantitative and qualitative research approaches was used to explore the survivorship experiences of patients and families who presented with an advanced stage of larynx cancer, where a total laryngectomy was indicated, implying removal of the entire larynx. Findings of the study reveal that patients and families mobilise both inner strengths and social support to adapt to inevitable physical changes that follow a laryngectomy.